Avaliação da gestão da fauna silvestre na comunidade de São João do Tupé (Manaus, Amazonas) pelo meio de um sistema de indicadores - Guillaume Antoine Marchand (Confins)
The management of the wild fauna has been ignored during a long time. Since the end of the 1990’s, some researchers and members of environmentalist NGO have been trying to fill the uncertainties that have been persisting in this domain. In fact, concrete and reliable data are scarce in domains such important as the state of animal resources, the sustainability of the hunting/fishing practices of the traditional populations or the efficiency of the procedures to protect threatened species… The present work aims to evaluate the quality of the management of the wild fauna provide through a system of indicators. This system is centered around four principals themes: the state of the habitat; the use of the fauna by local populations; the social, economic and cultural factors that may have an impact on the management; and, the social organization for the realization of this management. These four themes are divided in 13 indicators and 31 subindicators voluntarily simples to be manipulated and understood by everyone.  Applied to the field of study, these indicators show that despite progress in the protection of the habitat, the management of wildlife can still be improved in many ways, especially with regard to fishing or hunting practices, local population awareness to environmental protection measures and the implementation of control methods.